Industrial Microbial Technologies for Feed Protein Production from Non-Protein Nitrogen - Yuxin Ye; Yafan Cai; Fei Wang; Yi He; Yuxuan Yang; Zhengxiang Guo; Mengyu Liu; Huimin Ren; Shilei Wang; Dong Liu; Jingliang Xu; Zhi Wang (Microorganisms)
Due to the increasing global demand for feed protein, microbial protein has great potential of being able to feed sustainably. However, the application of microbial protein in the animal cultivation industry is still limited by its high cost and availability on scale. From the viewpoint of industrial production, it is vital to specify the crucial processes and components for further technical exploration and process optimization. This article presents state-of-the-art industrial microbial technologies for non-protein nitrogen (NPN) assimilation in feed protein production. Nitrogen sources are one of the main cost factors in the media used for large-scale microbial protein fermentation. Therefore, the available NPN sources for microbial protein synthesis, NPN utilization mechanisms, and fermentation technologies corresponding to the strain and NPN are reviewed in this paper. Especially, the random mutagenesis and adaptive laboratory evolution (ALE) approach combined with (ultra-) throughput screening provided the main impetus for strain evolution to increase the protein yield. Despite the underlying potential and technological advances in the production of microbial protein, extensive research and development efforts are still required before large-scale commercial application of microbial protein in animal feed.